Peripheral arterial disease: Exercise is medicineTM - Sorace, P.; Ronai, P.; Churilla, J.R. (ACSM's Health and Fitness Journal, 2010)
Learning objective: Peripheral arterial disease (PAD) significantly affects quality of life, particularly when doing activities such as walking and climbing stairs. In addition, persons with PAD have an increased risk for heart disease, stroke, and limb amputations. This article will summarize PAD, address exercise benefits specific to the disease, and discuss exercise training for those with PAD in both the clinical and the health and fitness setting. © 2010 Lippincott Williams & Wilkins.
1 citations (Crossref) [2023-10-31]
Keywords: Claudication; Functional Ability; Resistance Training; Stair Climbing; Walking; dept.hms

Evaluation of an interdisciplinary physically active lifestyle course model - Fede, Marybeth H. (Research Quarterly for Exercise and Sport, 2010)
tex.unique-id: ISI:000275436700043
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found

Pedagogical consideration: how do I teach to my students? - Xiang, Ping; Yang, Jinjin (Research Quarterly for Exercise and Sport, 2010)
tex.unique-id: ISI:000275436700013
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found